2009
DOI: 10.1007/s00439-009-0696-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of Down syndrome

Abstract: Down syndrome (DS) is caused by trisomy of all or part of human chromosome 21 (HSA21) and is the most common genetic cause of significant intellectual disability. In addition to intellectual disability, many other health problems, such as congenital heart disease, Alzheimer's disease, leukemia, hypotonia, motor disorders, and various physical anomalies occur at an elevated frequency in people with DS. On the other hand, people with DS seem to be at a decreased risk of certain cancers and perhaps of atheroscler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
191
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(208 citation statements)
references
References 144 publications
2
191
0
9
Order By: Relevance
“…For phenotypes found in all Down syndrome patients, the penetrance of each phenotype varies between patients (Antonarakis et al 2004). Despite the increasing amount of information available about the human genome and the availability of a mouse model for Down syndrome (O'Doherty et al 2005), the genes responsible for most of the phenotypes associated with Down syndrome are still unknown (Patterson 2007;Korbel et al 2009;Patterson 2009). Recently, detailed phenotypic analyses of as many as 30 aneuploid patients have allowed the identification of susceptibility regions for several specific phenotypes (Patterson 2007(Patterson , 2009; Korbel et al 2009;Lyle et al 2009), but the specific genes remain to be identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For phenotypes found in all Down syndrome patients, the penetrance of each phenotype varies between patients (Antonarakis et al 2004). Despite the increasing amount of information available about the human genome and the availability of a mouse model for Down syndrome (O'Doherty et al 2005), the genes responsible for most of the phenotypes associated with Down syndrome are still unknown (Patterson 2007;Korbel et al 2009;Patterson 2009). Recently, detailed phenotypic analyses of as many as 30 aneuploid patients have allowed the identification of susceptibility regions for several specific phenotypes (Patterson 2007(Patterson , 2009; Korbel et al 2009;Lyle et al 2009), but the specific genes remain to be identified.…”
mentioning
confidence: 99%
“…Despite the increasing amount of information available about the human genome and the availability of a mouse model for Down syndrome (O'Doherty et al 2005), the genes responsible for most of the phenotypes associated with Down syndrome are still unknown (Patterson 2007;Korbel et al 2009;Patterson 2009). Recently, detailed phenotypic analyses of as many as 30 aneuploid patients have allowed the identification of susceptibility regions for several specific phenotypes (Patterson 2007(Patterson , 2009; Korbel et al 2009;Lyle et al 2009), but the specific genes remain to be identified. Understanding the physiology of aneuploidy is not only relevant to those individuals with aneuploid genomes but also to understanding cancer since most cancerous cells are aneuploid (Matzke et al 2003;Pihan and Doxsey 2003;Storchova and Pellman 2004;Holland and Cleveland 2009;Williams and Amon 2009) or the consequences of copy number variation and dosage sensitivity (Dear 2009;Henrichsen et al 2009).…”
mentioning
confidence: 99%
“…With the advance of genetic engineering, it was no longer necessary to wait; these animals could be produced with the desired alterations, since the genetic causes of the disease in question were known. So, animals were produced that serve as models for studies of different types of cancers (Santos et al, 2008), heart disease (Moon, 2008), hypertension (Zadelaar et al, 2007), diabetes (Leroith and Gavrilova, 2006), obesity (BlĂŒher, 2005), osteoporosis (Klein, 2008), glaucoma (Zhou et al, 2008), blindness (Moussaif et al, 2006), deafness (Leibovici et al, 2008), Huntington's syndrome (Heng et al, 2008), Down's syndrome (Patterson, 2009), Parkinson's disease (Harvey et al, 2008), Alzheimer's disease (Gotz et al, 2009), anxiety (Kalueff et al, 2007, and depression (Kalueff et al, 2007).…”
Section: Use Of Genetically Modified Animals In Scientific Researchmentioning
confidence: 99%
“…Therefore, the next step is to examine the functions of the same somatosensory pathway (i.e., spinothalamic-mediated sensory functions of temperature, pain, and touch) in a large sample of adults with DS. Because individuals with Down syndrome form a heterogeneous group, with a mild to severe level of intellectual disability (Patterson, 2009) and an IQ ranging from 30 to 70 (Chapman & Hesketh, 2000), the level of intellectual functioning needs to be taken into account. The research questions of the present explorative study were: (1) are spinothalamic-mediated sensory functions (temperature discrimination, sharp-dull discrimination, and tactile threshold) in adults with DS different from general population control participants?…”
mentioning
confidence: 99%